Analysis of the Critical Success Factors for Ready-made Garments in Laghouat City - Mebarka Labiba; Widad Hachani; Adel Ladjali (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to determine the critical success factors for the ready-made garments in Laghouat, through elements that were expected as critical success factors represented in quality, cost, technology, marketing, and human resource efficiency. And to reach the goal of the study, data were collected by semi-structured interviews, observation, and content analysis for a sample of 10 successful workshops in the field, and then analyzing the obtained data represented in data related to Porter’s Five Forces analysis and others related to the expected success factors through the benchmarking method. Then deduce the strategic groups and test the hypotheses. The study reached results that showed the validity of the two hypotheses related to quality and cost, and the validity of other hypotheses in part related to technology, marketing, and human resource efficiency. Through this, we provided the workshop owners with advice represented in critical success factors for their activities and increasing their competitiveness, while identifying the strengths and weaknesses of each workshop and ways to manage weaknesses.